Repeated Detection of Bartonella DNA in Feline Placenta: Potential Implications for Placental and Fetal Development - Charlotte O. Moore; Ricardo Maggi; Kelli Ferris; Edward B. Breitschwerdt (Animals)
The domestic cat is the primary reservoir host of three flea-borne Bartonella species, one of which (Bartonella henselae) causes reduced fertility and reproductive failure in experimentally infected cats. Vertical transmission of Bartonella has been documented only in B-cell deficient mice, but not immunocompetent animals. As many free-roaming cats are chronically infected with Bartonella and may be immunocompromised by environmental stress or coinfection, we attempted to isolate Bartonella from the fetal and placental tissues of pregnant queens spayed during trap–neuter–release. Four samples from each tissue (ovary, uterus, fetus, and placenta) were split for direct DNA extraction, liquid culture, and culture on a blood agar plate. Samples from infected queens were inoculated into liquid media and sampled weekly for three weeks for DNA extraction and plating. Bartonella DNA was sequenced directly from 28% (5/18) of the free-roaming queens. For these five queens, liquid enrichment culture was attempted in duplicate for fetal and placental samples. Bartonella clarridgeiae DNA was amplified using qPCR liquid enrichment cultures from the placentas of two cats. These findings suggest that viable Bartonella organisms are present in feline reproductive tissue. Additional studies are needed to assess the transplacental transmission of Bartonella spp. and Bartonella’s influence on fetal development.